Assessment of Internal Damages in Sandwich Panels via Active Thermography - Andrzej KATUNIN; Monika CHUDA-KOWALSKA (Engineering Transactions, 2015)
Recently, the application of polymer-based composites in civil constructions and substitution of traditional materials by composites became a normal practice. Increasing applicability of composites, primarily sandwiches with soft cores, induces the development of the non-destructive testing methods used for the quality control and in-service inspection of the constructions made of such materials. In this study the internal damages, typical for the foam-core thick sandwich panels, that occur during manufacturing process as well as during in-service life were investigated. The description of internal damages was prepared based on real practical cases. Several types of damages were simulated in the foam-core sandwich panels, which were then tested using active thermography. Obtained results point to the great potential of this method in application for the damage assessment of structures and constructions made of these materials. The damages like cracks, partial local lacks of the core and debonding were successfully detected and localized. The method can be applied during inspections of civil structures being currently in operation and as a quality control method during manufacturing of these structures.